Effect of Heat Treatment on Microstructure and Properties of Improved 40CrNi2Si2MoV Steel. Issue 3 (3rd February 2023) - Tang, Yuanshou; Si, Yu; Yu, Shuoshuo; Xu, Zhengmeng; Cao, Pengjun; Li, Shouhua; Zhang, Longzhu; Li, Kejian
Abstract : Ultrahigh‐strength steel (2000 MPa) is a key material widely used in national defense, aerospace, and various other sectors. This kind of steel is more likely to break as its strength increases. To improve its toughness, it is crucial to fully understand the strengthening and toughening mechanisms, microstructural evolution characteristics, and heat‐treatment parameters of ultrahigh‐strength steel. Herein, an improved 40CrNi2 Si2 MoV test steel is designed based on the composition of the 40CrNi2 Si2 MoV ultrahigh‐strength martensitic steel and is subjected to quenching at 860/900/930/1050/1150 °C. The effects of microstructural changes on the test materials are analyzed using scanning electron microscopy, energy‐dispersive X‐ray spectroscopy, electron backscatter diffraction, transmission electron microscopy, and other characterization methods. The results show that at a quenching temperature of 1050 °C, the material exhibits an elongation of 8.2% and a strength as high as 2200 MPa owing to the coupled effects of complex multicomponent laths, substructures, dislocations, and nano‐precipitates. Abstract : A higher quenching temperature (1050 °C) is conducive to refining M6 C particle size and has little effect on the prior austenite grain size (PAGS). Therefore, the strength of 40CrNi2 Si2 MoV steel is significantly improved, and the loss of toughness is small. A high quenching temperature (1150 °C)is not conducive to PAGBS refinement, thus affecting the strength of steel.